Marketing strategy in education review as an effort to increase sales of dodol entrepreneurs (case study of dodol ria entrepreneurs in Tanjung Pura District) - Ulen Bangun (Lembaga Riset Mutiara Akbar, 2026)
The marketing strategy implemented by Dodol Ria entrepreneurs in Tanjung Pura District to increase sales is based on the 4P marketing mix framework, which consists of product, price, place, and promotion strategies. In terms of place strategy, Dodol Ria operates in a strategic industrial location that is easily accessible to consumers, thereby supporting distribution efficiency and market reach. Regarding promotion strategy, Mrs. Sulastri collaborates with resellers to expand market coverage. In addition, consumers can place orders through social media platforms such as Instagram and WhatsApp, which facilitates easier access to Dodol Ria products and enhances customer convenience. By consistently implementing these four components of the marketing mix, Dodol Ria in Tanjung Pura District has been able to sustain its business operations, generate profits, and continue expanding its market presence. Maintaining product quality remains a key priority, as the existing quality standards are already well established. However, further innovation is necessary, particularly in diversifying flavor variants, to meet consumer preferences and stimulate continued growth in dodol sales.